Climate change impacts and renewable energy innovation : a firm-level analysis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, Auckland, New Zealand - Rastegar, Hiva (Massey University, 2024)
Amidst the escalating challenges posed by climate change, the transition to renewable energy emerges as a pivotal strategy for businesses and organisations to reduce environmental footprints and enhance sustainability. Against this backdrop, this thesis delves into the complex interplay between climate change impacts and firms' pursuit of renewable energy innovation, drawing on the Behavioural Theory of the Firm. Concentrating on the specific impact of climate change-induced natural disasters, this research investigates their direct influence on firms’ pursuit of renewable energy innovation, while also considering the moderating effects of market dynamics. With climate change posing unprecedented risks and opportunities for businesses, understanding these dynamics becomes crucial for developing effective strategies and policies to foster sustainable practices. Employing a quantitative methodology, this study scrutinises the behaviour of U.S. firms following climatological disasters from 2013 to 2018, using a Difference-in-Differences model complemented by meta-analysis. The findings reveal that climatological disasters significantly motivate firms to pursue renewable energy innovation. The study also identifies that the pursuit of renewable energy innovation by peer firms is identified as a significant influence, underscoring the influence of industry trends and competitive behaviour on corporate innovation pathways. This contrasts with other market dynamics; investor sentiment and media coverage were found not to have a significant effect on firms’ renewable energy innovation post-disaster. In a deeper exploration of the factors moderating the effect of climatological disasters on renewable energy innovation, the research unveils that firms falling below their performance aspirations are more likely to intensify their pursuit of renewable energy innovation post-disasters, viewing innovation as a solution to narrow the performance gap. Additionally, subsidiaries of foreign multinational enterprises demonstrate a less pronounced increase in renewable energy innovation compared to domestic firms, indicating that firm origin significantly affects their pursuit of innovation following climatic events. Further, natural disaster uncertainty emerges as a significant determinant, affecting the propensity for renewable energy innovation in a context marked by unpredictability. Lastly, a firm’s history of natural disasters influences its approach to renewable energy innovation, suggesting that past experiences could foster a foundation of resilience or engender a posture of strategic prudence. The thesis contributes to the academic literature by offering new insights into the interplay between climate change impacts and renewable energy innovation, highlighting the complexity of firms’ behaviour following environmental challenges. It deepens the Behavioural Theory of the Firm by integrating the threat rigidity model to explain how firms behave following climate change impacts. The significance of this study extends beyond its academic contributions, providing a roadmap for climate action that enables policy-makers, business leaders, and stakeholders to effectively tackle the ongoing climate change crisis. The research offers guidance on how firms can leverage local insights and past disaster experiences to enhance their pursuit of RE innovation following climate change-induced natural disasters. It suggests that both domestic firms and multinational enterprises need targeted strategies that align with their operational contexts and previous experiences. The policy implications advocate targeted support that aligns with the distinct needs of domestic firms and multinational enterprises, thereby facilitating a more tailored and effective pursuit of RE innovation post-climatological disaster. Policies should promote the integration of natural disaster risk assessments into strategic planning, support collaborative innovation efforts, and enforce transparency in reporting RE innovation. These policy recommendations are designed to directly contribute to Sustainable Development Goals 7 (affordable and clean energy) and 13 (climate action), by enhancing energy security, promoting sustainable energy use, and fostering innovation to combat climate change impacts. This highlights the study’s pivotal role in contributing to sustainable development and achieving climate action goals.
Keywords: climate change-induced natural disasters, renewable energy innovation, behavioural theory of the firm (BTOF); 350701 Corporate governance; 350705 Innovation management